PENGARUH PROMOSI TERHADAP TINGKAT PENJUALAN SEPEDA MOTOR HONDA BeAT PADA PT DAYA ADICIPTA WISESA DI MAUMBI MINAHASA UTARA - ROLANDO DIEMER MUSAK; HANNY SUMAMPOUW; JOHNY TAMPI (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACT : The research in based on the notion that Promosion is one of the important activities of the Maerketing Mix. Because the campaign is an activity the companyinits effort to communicate with consumers. With the expected existing communication in answer frm consumer on product offered. This response by consumers can be categorized in the readiness of the buyer, ie awareness, knowledge, interests, preferences, believe, to buy. For the main purpose of the sale, namely : inform, persuade/ influence and remain. The purpose og this study was to determine the effect on the rate of sales promotion motor Honda Beat bikes at PT DayaAdiciptaWisesa in maumbi North Minahasa Manado. This research uses descriptive method kualitatif using Descriptive Statistics analysis using a simple correlation analysis and simple regression. Keywords : Promotional Sales Rate